2011
DOI: 10.1075/sic.8.2.01cla
|View full text |Cite
|
Sign up to set email alerts
|

¿Constituyen las Antillas y el Caribe continental una sola zona dialectal?

Abstract: ¿Constituyen las Antillas y el Caribe continental una sola zona dialectal?Datos de la variable expresión del sujeto pronominal en San Juan de Puerto Rico y Barranquilla, Colombia* Jeroen Claes Aunque la variación entre sujetos explícitos y tácitos se ha investigado en dialectos del español (Cameron 1995; Orozco y Guy 2008), no contamos con estudios contrastivos entre dos variedades caribeñas. Sin embargo, tal comparación podrá arrojar nueva luz sobre las zonas dialectales de América (cf. Otheguy, Zentella y Li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
9

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(12 citation statements)
references
References 6 publications
0
3
0
9
Order By: Relevance
“…These results imply that the effects of TMA are similar across Mexico. These tendencies are further commensurate with what occurs throughout the Hispanic World in monolingual speech communities (Abreu 2009(Abreu , 2012Cameron 1993;Claes 2011;Orozco 2015;Travis 2005bTravis , 2007; among others) as well as in situation of contact with other languages (Bayley & Pease-Álvarez 1997;Erker & Guy 2012;Hochberg 1986;Shin & Erker 2015:180). Thus, our results support the premise that morphologically ambiguous verbal paradigms such as the imperfect tense promote more overt pronominal subjects than unambiguous forms.…”
Section: Grammatical Person and Number Of The Subjectmentioning
confidence: 71%
“…These results imply that the effects of TMA are similar across Mexico. These tendencies are further commensurate with what occurs throughout the Hispanic World in monolingual speech communities (Abreu 2009(Abreu , 2012Cameron 1993;Claes 2011;Orozco 2015;Travis 2005bTravis , 2007; among others) as well as in situation of contact with other languages (Bayley & Pease-Álvarez 1997;Erker & Guy 2012;Hochberg 1986;Shin & Erker 2015:180). Thus, our results support the premise that morphologically ambiguous verbal paradigms such as the imperfect tense promote more overt pronominal subjects than unambiguous forms.…”
Section: Grammatical Person and Number Of The Subjectmentioning
confidence: 71%
“…The variable presence vs. absence of subject pronouns with finite verbs has been extensively investigated in communities throughout the Hispanophone world (Guitart 1982, Silva-Corvalán 1982, Cameron 1993, Bayley and Pease-Alvarez 1997, Flores-Ferrán 2002, Orozco and Guy 2008, Torres Cacoullos and Travis 2010, Claes 2011, Holmquist 2012, Otheguy and Zentella 2012, Shin 2014, Michnowicz 2015, Carvalho et al 2015. Despite widely shared norms in terms of linguistic factors that condition the presence or absence of pronouns, regional differences in overall rates of pronoun use are routinely reported (Lipski 1994:221, Otheguy et al 2007.…”
Section: The Presence Vs Absence Of Subject Pronounsmentioning
confidence: 99%
“…Third, there is nothing sacrosanct about national origin as a tool for identifying dialectal groupings. For example, there appears to be wide variation within Colombia, and scholars have argued that the Spanish spoken on the Colombian coast shares many features with that of Cuba, Puerto Rico, and the Dominican Republic (Lipski 1994:6;Orozco & Guy 2008; but also see Claes 2011). 8 An anonymous reviewer suggested that social class should include more than two categories.…”
mentioning
confidence: 99%